Motivasi Belajar Bahasa Mandarin sebagai Bahasa Kedua - Yi Ying; Muhammad Nanang Suprayogi; Evi Afifah Hurriyati (Humaniora, 2013)
The goals of article was to explore students’ main motivation in learning Mandarin as second language acquisition and the difference motivation between Chinese-descending and non-chinese students. There were 276 respondents chosen by purposive sampling from three universities. They were students from Mandarin Department of Bina Nusantara University, Jakarta, Darma Persada University, Jakarta, and North Sumatera University, Medan. A cooperation on deciding research instruments was collaborated with Faculty of Tionghoa Language and Literature of Huaqiau University, China. Descriptive analysis was done to explore students’ main motivation in learning Mandarin, continued by different tests to know the different motivation between native and descending students. Research results indicated that the motivation in learning language is low; there is no significant difference between integrative and instrumental motivation. Also, there was no motivation significant different between chinese-descending dan non-chinese students in learning Mandarin. Lecturers should develop their methods of teaching to develop students’ learning motivation in learning Mandarin.